MANAJEMEN PROYEK, IMPLEMENTASI, DAN INVESTASI SISTEM INFORMASI MANAJEMEN SUMBER DAYA MANUSIA - Intan Amalia; Sukmawaty Nurcahyani; Yulia Haerani; Zahra Aliipah; Reni Widyastuti (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
The rapid development of information technology has brought significant changes in the way organizations manage human resources. Human Resource Management Information Systems (HRMIS) are a strategic solution to help organizations integrate, manage, and utilize HR data effectively and efficiently. However, the success of HIS (Human Information Systems) implementation is not only determined by the sophistication of the technology used, but is also greatly influenced by how the system project is managed, implemented, and supported through appropriate information investment. The results show that the application of structured project management can minimize the risk of project failure, such as cost overruns, delays, and system incompatibility with user needs. In addition, the implementation of a well-planned system and long-term information investment play an important role in ensuring the sustainability and effectiveness of SIM-SDM. With good integration between project management, implementation, and information investment, SIM-SDM can provide strategic benefits in the form of increased operational efficiency, data accuracy, quality of decision making, and organizational competitiveness in the digital era